Customers' Views on the Implementation of a Farmers Market Incentive Program: Successes and Opportunities for Improvement. Issue 4 (4th July 2021) - Headrick, Gabby; Hecht, Amelie A.; Misiaszek, Caitlin; Brosius, Shelley; Crone, Amy; Surkan, Pamela J.
ABSTRACT: We explored customer perspectives of a farmers market incentive program for nutrition assistance beneficiaries in Maryland. Surveys were completed by a purposive sample of customers (n = 279) from four farmers markets. A sub-sample (n = 106) completed semi-structured interviews on barriers and facilitators to program use. Facilitators included availability of universal incentive tokens across markets, increased spending power, knowledgeable market staff, ability to purchase different food items, and an inviting market environment. Barriers included limited program promotion, limited explanation of program logistics, confusion over acceptable purchases, and funding running out. These findings can inform implementation of similar incentive programs.